Glymphatic dysfunction associated with cortisol dysregulation in major depressive disorder - Shengli Chen; Ziyun Xu; Zheng Guo; Shiwei Lin; Hongyuan Zhang; Qunjun Liang; Qianyun Chen; Yingli Zhang; Bo Peng; Yanzhen Zhao; Gangqiang Hou; Yingwei Qiu (Translational Psychiatry)
Abstract Cortisol dysregulation plays a critical role in the pathophysiology of depression, but its exact impact on the brain remains unclear. In this cross-sectional study, 210 participants, including 164 depressed patients and 46 healthy controls (HCs), were assessed. Glymphatic circulation was evaluated on Magnetic Resonance Imaging via choroid plexus (CP) volume fraction, perivascular space (PVS) volume fraction, fractional volume of extracellular-free water (FW), and diffusion tensor imaging along the perivascular space (DTI-ALPS) index. Chemiluminescence was employed to analyze the cortisol levels in a sub-cohort of the patients. Independent sample t-tests and Pearson’s correlation analysis were used to assess differences in these metrics between groups and their correlation with cortisol levels. After adjusting for age, sex, years of education, and total intracranial volume, depressed patients exhibited a significantly higher FW and lower ALPS than HCs. No significant differences were found in CP volume and PVS fraction between depressed patients and HCs. Additionally, the increased FW correlated positively with cortisol levels in depressed patients, suggesting that glymphatic dysfunction is linked to plasma cortisol levels in depression.